Decreases in global beer supply due to extreme drought and heat. (November 2018) - Xie, Wei; Xiong, Wei; Pan, Jie; Ali, Tariq; Cui, Qi; Guan, Dabo; Meng, Jing; Mueller, Nathaniel; Lin, Erda; Davis, Steven
Abstract Beer is the most popular alcoholic beverage in the world by volume consumed, and yields of its main ingredient, barley, decline sharply in periods of extreme drought and heat. Although the frequency and severity of drought and heat extremes increase substantially in range of future climate scenarios by five Earth System Models, the vulnerability of beer supply to such extremes has never been assessed. We couple a process-based crop model (decision support system for agrotechnology transfer) and a global economic model (Global Trade Analysis Project model) to evaluate the effects of concurrent drought and heat extremes projected under a range of future climate scenarios. We find that these extreme events may cause substantial decreases in barley yields worldwide. Average yield losses range from 3% to 17% depending on the severity of the conditions. Decreases in the global supply of barley lead to proportionally larger decreases in barley used to make beer and ultimately result in dramatic regional decreases in beer consumption (for example, −32% in Argentina) and increases in beer prices (for example, +193% in Ireland). Although not the most concerning impact of future climate change, climate-related weather extremes may threaten the availability and economic accessibility of beer. The vulnerability of barley production and beer supply to future weather extremes remains unknown. A study using modelling finds that weather extremes associated with climate change would threaten the availability and economic accessibility of beer.